An Oxidant-Free and Mild Strategy for Quinazolin-4(3H)-One Synthesis via CuAAC/Ring Cleavage Reaction - Yueling He; Zhongtao Yang; Danyang Luo; Xiai Luo; Xiaodong Chen; Weiguang Yang (Molecules, 2023)
An oxidant-free and highly efficient synthesis of phenolic quinazolin-4(3H)-ones was achieved by simply stirring a mixture of 2-aminobenzamides, sulfonyl azides, and terminal alkynes. The intermediate N-sulfonylketenimine underwent two nucleophilic additions and the sulfonyl group eliminated through the power of aromatization. The natural product 2-(4-hydroxybenzyl)quinazolin-4(3H)-one can be synthesized on a large scale under mild conditions with this method.